FEM analysis of a DCP implant on a human femoral bone - Thongchai Fongsamootr (2018)
Healing of femoral fractures commonly involves the use of a steel prosthesis and invasive surgery. The determination of prosthesis type and dimensions is still made by surgeons according to empirical data. In order to reduce the occurrence of failures of the steel components it is important to study geometrical and material influences on system resistance. The bearing of the total body weight by the bone before complete healing is a commonly observed cause of healing failure. This study focuses on one type of the implant used in clinical institutions: the Dynamic Compressive Plate (DCP) fixed on the bone with screws. We studied the influence of 3 geometrical parameters: (1) the length of the DCP fixed with two screws, (2) the number of screws and the different positioning patterns with a 200mm plate length, and (3) the influence of the fracture gap size between the two broken parts of the bone on the stress distribution. The analysis was based on a realistic geometry of a human left femur using the Finite Element Method (FEM). Plate and screws were modeled and assembled on the bone loaded with vertical and horizontal forces on the hip region. Results show that all of these parameters have a significant influence, but the number of screws and their positioning seem to be most decisive while the length is a less significant design parameter. Finally the appliance of a simulated fracture gap produces a huge increase of the stress value in part. The model needs further development to discuss about these results because many approximations has been made that avoid the results to be reliable, and further studies will come to complete them.